Logistics around the meat supply chain in Kruger National Park : the African savanna buffalo (Syncerus caffer caffer) as model - Van As, Jan Singleton (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScFoodSc)--Stellenbosch University, 2019.